Implementasi Rencana Pembangunan Jangka Menengah Desa Sebagai Kerangka Acuan Pembangunan Desa - Setiawan, Rahmad; Amiruddin, Denie; Kurniawan, Heru Yudi; Febriany, Tri Atika (Res Judicata, 2024)
This study aims to determine how the process of determining the Village Medium-Term Development Plan in Sandai Kanan Village and Muara Jekak Village. In addition, this study also aims to determine the process of determining the Village Medium-Term Development Plan and the Implementation of Village Development in Sandai Kanan Village and Muara Jekak Village, Ketapang Regency. This research uses descriptive qualitative research, with data collection techniques through observation and interviews. The primary data sources in this study are the informant respondents Uti Fahrul, the secretary of the right sandai village and Andri Suandi, the secretary of the Muara Jekak village and supported by primary, secondary and tertiary legal materials. The results showed that in Sandai Kanan Village and Muara Jekak Village in the process of determining the RPJMDes 2017-2022 as stipulated in Law No. 6 of 2014 has been carried out quite well, this is confirmed by supporting data, namely PerDes on RPJMDes in both villages. Regarding the process of implementing development in Sandai Kanan Village, in particular, it does not run as it should, this is confirmed by the data obtained, namely the RPJMDes data in development is not implemented. As for Muara Jekak Village, the implementation process has been carried out in accordance with the data that has been obtained and corroborated by the results of interviews and observations by going directly to the field.